Prevalence and Detection of Trichomonas vaginalis in HIV-Infected Pregnant Women. Issue 5 (May 2018) - Price, Collin M.; Peters, Remco P.H.; Steyn, Janré; Mudau, Maanda; Olivier, Dawie; De Vos, Lindsey; Morikawa, Erika; Kock, Marleen M.; Medina-Marino, Andrew; Klausner, Jeffrey D.
Abstract : Background: Trichomonas vaginalis is a sexually transmitted infection associated with increased transmission of HIV and significant adverse birth outcomes; culture and polymerase chain reaction (PCR) are commonly used in diagnosis. Methods: Consenting HIV-infected pregnant women were recruited from clinics in South Africa and screened for T. vaginalis using PCR. Polymerase chain reaction–positive women provided an additional sample for culture. We compared T. vaginalis detection between PCR and culture, and investigated how PCR cycle threshold (Ct) values differ among culture results. Results: A total of 359 women were enrolled and 76 (20%) tested T. vaginalis PCR positive. Cultures were obtained from 61 of the PCR-positive women, and 38 (62%) were culture positive. The median baseline Ct of the PCR-positive/culture-positive group was 22.6 versus 38.0 among those who were PCR positive/culture negative ( P < 0.001). Culture-positive cases had lower Ct values (higher DNA load); a Ct value less than 30 predicted positivity with a sensitivity of 97% and a specificity of 96%. Conclusions: Culture was positive in roughly half of PCR-positive cases. The culture-negative cases had significantly higher Ct values, indicating a lower concentration of T. vaginalis DNA. A Ct value of 30 provides a reliable threshold for predicting culture positivity. The clinical significance of culture-negative infections detected by PCR is still unclear. Abstract : Among HIV-infected pregnant women in South Africa, culture-detected Trichomonas vaginalis in only a portion of polymerase chain reaction–positive cases, and cycle threshold values proved valuable in the interpretation of polymerase chain reaction results.